MANAJEMEN PEMBINAAN EKSTRAKURIKULER OLAHRAGA MA DI KABUPATEN DEMAK (Indonesian Journal for Physical Education and Sport, 2020)
The focus of this research was to find out Sport Extracurricular Development in Public Vocational Schools in Demak Regency.This study used qualitative research with a descriptive approach. The data sources of this study were the Principal or Student, Physical Education Teacher and the sport extracurricular participants. Data analysis methods that were carried out continuously included data reduction, data presentation and data verification. The results of the study were as follows: (1) planning is said to be good from suppliers, nurseries, facilities, development and funding. (2) organization is said to be good as seen from the organizational structure according to roles and responsibilities. (3) good results come from the exercise program and execise schedule and activities that are carried out. (4) surveillance is said to be good in terms of evaluation and quality work standards.